2005
DOI: 10.1007/s10519-005-9006-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Linkage and Association Analyses of the 124-bp Allele of Marker D2S2944 with Anxiety, Depression, Neuroticism and Major Depression

Abstract: A central issue in psychiatric genetics is whether positive findings replicate. Zubenko et al. (2002b, Mol. Psychiatry 7:460-467) reported an association of the 124-bp allele of D2S2944 with recurrent early-onset major depression for females. We tested for association of this allele to continuous measures of anxiety, depression and neuroticism in a Dutch sample of 347 males and 448 females, and to DSM-IV major depression in a subsample of 210 males and 295 females. The association of the 124-bp allele to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002). Due to the high level of comorbidity between alcohol and drug dependence and major depression, and as indexed by a high LOD score of 3.49 for comorbid alcoholism and major depression in prior linkage analyses using COGA data (Nurnberger, Jr. et al, 2001), this region on chromosome 2 may be tapping into a region of susceptibility for both disorders.…”
Section: Discussionsupporting
confidence: 58%
“…Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002). Due to the high level of comorbidity between alcohol and drug dependence and major depression, and as indexed by a high LOD score of 3.49 for comorbid alcoholism and major depression in prior linkage analyses using COGA data (Nurnberger, Jr. et al, 2001), this region on chromosome 2 may be tapping into a region of susceptibility for both disorders.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, past studies have suggested for substantial overlap of the genetic factors influencing liability to a wide range of internalizing disorders (Hettema et al, 2006). Comparing our results to those from linkage scans of suicide attempts (Willour et al, 2007), neuroticism (Beem et al, 2006), bipolar disorder (Marcheco-Teruel et al, 2006), panic disorder (Gelernter et al, 2001), and anorexia nervosa (Devlin et al, 2002) indicates some overlap with our reported regions.…”
Section: Discussionsupporting
confidence: 54%
“…Philibert et al 2003 confirmed the selective association of the D2S2944 124 bp allele among women with RE‐MDD, while Langbehn et al 2006 reported an association of this allele with MDD complicated by alcohol abuse/dependence and/or antisocial personality disorder. Beem et al 2006, following up a finding of suggestive linkage (LOD∼1.5) of neuroticism to the region containing CREB1 , reported a nominally significant ( P = 0.04) sex‐specific association for anxiety in males that did not survive correction for multiple testing.…”
Section: Discussionmentioning
confidence: 99%